Stress as an Integral Part of Our Life - Metreveli, Lia; Japaridze, Ketevan (European Scientific Journal, ESJ, 2022)
The modern world is full of stressors. Dealing with these stressors and being satisfied with life is the most important goal of almost everyone. Stress is an inevitable phenomenon in people’s daily life. We constantly have to face, deal with and adapt to many stressful situations. The main goal of every person is the feeling of satisfaction with life, therefore, it is important to learn to cope effectively with stress in order to avoid the complications that accompany a stressful event for a long time. Each person is individual and therefore uses different methods to cope with stress. The report discusses stress as an integral part of human life, how it affects the development of the individual, how it affects the biological systems of the human body and the psyche as a whole. The reason for our conflict with the outside world is explained, as well as why there are many events and circumstances in our lives that cause us to react to stress. We tried to learn ways to overcome it. However, whether this provocation develops further, answers Iissiidiology, which offers a new face of this problem. The connection between depression and stress. The purpose of my study was to determine the general level of stress in a certain part of the population and to study the relationship between stress and depression. It is noteworthy that all our lives are related to stress in one way or another. Unfortunately, human life does not exist without stressful situations, stress accompanies all spheres of human activity, its existence is beyond doubt. It is significant that stress has a significant impact on both physical health and mental state, social-psychological functions of a person. It is reflected in all aspects of our creative life and leaves a certain and quite serious mark on all our possibilities and ways of interacting with the outside world. In the conditions of the Covid-19 pandemic, problems related to psychological well-being are especially relevant for the modern world. In reality, the problems created by the pandemic lead to an increase in stress, anxiety and depression rates in society, which may become a determinant of a pessimistic attitude towards life, a decrease in self-confidence, a loss of faith in the future, and a change in life goals and values (Kekelia, Kereselidze, Shanava 2021).